Pengaruh Tingkat Pendidikan dengan Pengetahuan Petugas Rekam Medis Tentang Sensus Harian Rawat Jala di Rumah Sakit Stikes Elisabeth Medan - Prilia Hia (Yayasan Literasi Sains Indonesia, 2022)
The daily outpatient census is an activity of recording or calculating patients that is carried out every day at each outpatient installation. The daily census of patients is carried out every day. This is so that the hospital can find out how many patients visit each day. The population used is all medical record officers at Santa Elisabeth Hospital Medan with a sample of 10 people. This type of research is descriptive research. The instruments used are interviews and observations. Descriptive data analysis. The results obtained that medical record officers with good knowledge (60%) and enough (40%) it can be concluded that the level of knowledge of a medical record officer is influenced by the level of education received by each officer in order to create better performance and results. in patient care. It is recommended to hospitals to improve the quality of human resources, provide motivation, make plans for human resource needs based on the workload of medical recorders.